A numerical investigation of thermal engine encapsulation concept for a passenger vehicle and its effect on fuel consumption. (February 2019) - Minovski, Blago; Andrić, Jelena; Löfdahl, Lennart; Gullberg, Peter
Increasingly tough regulations for emission levels and a growing demand for an environmentally clean motor industry impose high requirements in modern automotive development. During recent decades, carmakers have been utilizing various strategies to minimize energy losses in the powertrain to meet legislative and market demands. A great part of research efforts has been focused on improving engine performance during cold starts characterized by increased friction losses. Thermal engine encapsulation is an effective design choice to reduce engine friction in applications with frequent cold starts. In the present work, a coupled 1-D–3-D system-level approach is used to investigate the effects of a novel engine-mounted encapsulation concept featuring air shutters on fuel consumption in a Volvo S80 passenger vehicle. Simulations are performed for sequences of the Worldwide harmonized light vehicles test cycle (WLTC) drive cycle, which include different time intervals of engine inactivity when the car is parked in air of an quiescent ambient temperature. The results show that engine encapsulation with high area coverage (97%) can retain engine oil temperature above 19°C for up to 16 h after engine shutdown at an ambient temperature of 5°C, leading to 2.5% fuel saving during engine warm-up when cold starts occur between 2 and 8 h after key-off. Encapsulations with a lower area coverage (90%) have proven to be less effective, with fuel saving of 1.25% as the temperatures of the oil and engine structures decrease more quickly after key-off compared to the fully enclosed encapsulation.